2020
DOI: 10.1002/chem.202000079
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism and Origin of MAD‐Induced Ni/N‐Heterocyclic Carbene‐Catalyzed Regio‐ and Enantioselective C−H Cyclization of Pyridines with Alkenes

Abstract: This work presentsaDFT-based computational study on the regio-ande nantioselective CÀHf unctionalization of pyridines with alkenes at the relatively unreactiveC 4position, whichw as successfully achieved by Shi et al. [J. Am. Chem. Soc. 2019, 141,5 628-5634] using Ni 0 /N-heterocyclic carbene( NHC) catalysis undert he assistanceo fa na luminum-based Lewis acid additive (2,6-tBu 2 -4-Me-C 6 H 2 O) 2 AlMe (MAD).T he calculationsi ndicate that the selectivef unctionalizationi nvolves at hree-step mechanism in w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…This is mainly due to the difference in the energy of the LLHT transition state and Ni­(NHC)­(alkene) ( 4a or 4b ) (Figures and ). Herein, we carried out the distortion–interaction analysis , to give insights into the regioselectivity for the formation of the linear product P1 (Table ). The distortion energies Δ E dist (Ni­(NHC)­(alkene)) and Δ E dist (pyridine-AlMe 3 ) were calculated from the difference between the energy of the distorted structure of each fragment taken from the LLHT transition state structure and the energy of each optimized structure.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is mainly due to the difference in the energy of the LLHT transition state and Ni­(NHC)­(alkene) ( 4a or 4b ) (Figures and ). Herein, we carried out the distortion–interaction analysis , to give insights into the regioselectivity for the formation of the linear product P1 (Table ). The distortion energies Δ E dist (Ni­(NHC)­(alkene)) and Δ E dist (pyridine-AlMe 3 ) were calculated from the difference between the energy of the distorted structure of each fragment taken from the LLHT transition state structure and the energy of each optimized structure.…”
Section: Resultsmentioning
confidence: 99%
“…In combination with the experimental results, density functional calculations have been widely used to elucidate reaction mechanisms of Ni-catalyzed hydroelementation reactions. In addition to the OA/MI and CMD mechanisms, recent density functional studies showed that hydroarylation and hydroalkenylation of alkenes and alkynes catalyzed by Ni complexes proceed via a ligand-to-ligand H-transfer (LLHT) pathway. In the LLHT pathway, aromatic C–H bond activation occurs by direct H-transfer from the arene to alkene/alkyne; subsequently, the hydroarylation product is reductively eliminated. The alkene/alkyne plays the role of a hydrogen acceptor in the LLHT mechanism similar to what a Lewis base does in the CMD mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…To elucidate the detailed mechanism and origins of the enantioselectivity, we performed DFT-based first-principles calculations for the reaction denoted by entry 7 in Table at the B3LYP-D3­(BJ)/LANL2DZ-6-311+G­(d,p)/SMD­(cyclohexane)//B3LYP-D3­(BJ)/LANL2DZ-6-31G­(d,p)/SMD­(cyclohexane) level. According to the previous reports, , the reaction could follow a ligand-to-ligand hydrogen transfer (LLHT) mechanism. As indicated by calculated Gibbs energy profiles (Figure ), the reaction goes through three stages: substrate coordination, LLHT, and C–C reductive elimination.…”
Section: Resultsmentioning
confidence: 97%
“…46 DFT calculation was also conducted to further understand the detailed reaction mechanism. 47 C-H activation and alkene insertion proceeded simultaneously in one elementary step, suggesting an LLHT mechanism in the catalytic cycle. And the origin of the preferential R-configuration product was the smaller H-H repulsion effect in the transition state.…”
Section: Template For Synthesis Thiemementioning
confidence: 94%